(untitled) (Journal of the College of Basic Education, 2022)
Elements of Art is one of the most important subjects in the life of students because it represents a key factor in building the components of an artistic painting. Therefore, teaching this subject requires accuracy and high attention by providing all educational requirements to provide the learner with its artistic concepts, and by identifying the difficulties faced by the subject teachers. The elements of art from the point of view of the students of the Department of Education, College of Fine Arts, University of Diyala, represents a scientific evaluation work that helps in the development of the educational process, and standing on the opinion of the arbitrators in identifying these difficulties and their contribution to the expression of facilitating their treatment, as well as motivating the researcher to do her research.